Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6 +7

1 answer

h(x) = (x - 3)^2 - 2
Similar Questions
  1. Cole rewrote a quadratic function in vertex form. h(x)=x^2 -6x+7Cole said that the vertex is (3, 2). Is Cole correct? If not,
    1. answers icon 1 answer
    1. answers icon 3 answers
  2. Cole rewrote a quadratic function in vertex form.h(x)= x2−6x+7 Step 1: h(x)= (x2−6x+ 9 )+7 Step 2: h(x)=(x2−6x+ 9 )+7 −9
    1. answers icon 1 answer
  3. April rewrote a quadratic function in vertex form.h(x)=5^2-30x+30 step 1 h(x)=5(x^2-6x+ )+30 step 2 h(x)=5(x^2-6x+9)+30-45 step
    1. answers icon 2 answers
more similar questions